2022
DOI: 10.1186/s12876-022-02317-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Analysis of antiviral efficacy after switching from brand to generic entecavir in patients with treatment-naïve chronic hepatitis B

Abstract: Background/Aims Entecavir (ETV) can suppress chronic hepatitis B (CHB) virus replication as a standard of treatment drugs. For the treatment of CHB, affordable generic drugs may be more widely used in developing and undeveloped countries. However, there is little real-world data regarding the clinical efficacy of switching from entecavir-brand-name drugs (ETV-Brand) to entecavir generic drugs (ETV-Generic) with 0.5 mg once daily. The aim of the study was to evaluate the antiviral activity and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Hence, the article does not adhere to the journal's second publication criterion or PLOS' Editorial policies pertaining to text reuse and publication of related studies, and concerns remain regarding partial redundancy of the two articles [1,2].The ethics approval number (210202) in [1] is also reported in several articles by some of the same authors, including [3-7], which describe studies and patient cohorts different to those reported in [1]. Additionally, discrepancies were identified between the description of the study design in [1] and the ethics approval documentation provided during discussions.The first author stated that the same approval number (210202) was obtained for multiple different studies [1,[3][4][5][6][7] as the applications for approval for all the studies were made to the IRB together. They also acknowledged that the study described in [1] was retrospective, which conflicts with the description of the study design in [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the article does not adhere to the journal's second publication criterion or PLOS' Editorial policies pertaining to text reuse and publication of related studies, and concerns remain regarding partial redundancy of the two articles [1,2].The ethics approval number (210202) in [1] is also reported in several articles by some of the same authors, including [3-7], which describe studies and patient cohorts different to those reported in [1]. Additionally, discrepancies were identified between the description of the study design in [1] and the ethics approval documentation provided during discussions.The first author stated that the same approval number (210202) was obtained for multiple different studies [1,[3][4][5][6][7] as the applications for approval for all the studies were made to the IRB together. They also acknowledged that the study described in [1] was retrospective, which conflicts with the description of the study design in [1].…”
mentioning
confidence: 99%
“…The first author stated that the same approval number (210202) was obtained for multiple different studies [1,[3][4][5][6][7] as the applications for approval for all the studies were made to the IRB together. They also acknowledged that the study described in [1] was retrospective, which conflicts with the description of the study design in [1].…”
mentioning
confidence: 99%